2008
DOI: 10.17660/actahortic.2008.800.61
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Alternative European Pear Cultivars for U.S. West Coast Growers

Abstract: California, Oregon, and Washington produced 98% of the commercial U.S. pear crop from 2003-2005, consisting of 'Williams' ('Bartlett') (51%), 'Beurré Anjou' (36%), 'Beurré Bosc' (11%) and 2% others, mainly 'Doyenne du Comice', 'Red Clapp's Favorite', 'Seckel' and 'Concorde'. Declining processing demand has heightened interest and evaluation of new fresh market alternatives. Production, post-harvest quality, and consumer sensory evaluation data from 2001 to 2006 has allowed identification of several new potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Overall, the main contributions of this study suggest the pear industry should seek to deliver pears with the attributes desired by consumers, which include sweetness, juiciness, and a softer texture. These attributes have been shown by previous researchers (Colonna et al, 2023;Elkins et al, 2006Elkins et al, , 2008Gallardo et al, 2023;Steyn et al, 2011;Taiti et al, 2017;Torregrosa et al, 2019;Turner et al, 2005) to be highly desirable to pear consumers. However, the pear industry should also consider introducing pears with other sensory attributes as the present results suggested that there is consumer interest.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, the main contributions of this study suggest the pear industry should seek to deliver pears with the attributes desired by consumers, which include sweetness, juiciness, and a softer texture. These attributes have been shown by previous researchers (Colonna et al, 2023;Elkins et al, 2006Elkins et al, , 2008Gallardo et al, 2023;Steyn et al, 2011;Taiti et al, 2017;Torregrosa et al, 2019;Turner et al, 2005) to be highly desirable to pear consumers. However, the pear industry should also consider introducing pears with other sensory attributes as the present results suggested that there is consumer interest.…”
Section: Discussionsupporting
confidence: 71%
“…Consumer sensory evaluation of pears in Oregon and Northern California (n = 2700) showed that overall liking was driven by sweetness and flavor (Elkins et al, 2006). Researchers have also found that sweetness and texture are important sensory properties that influence the liking of cultivars, while gritty texture and lack of flavor are key attributes driving disliking of pears (Elkins et al, 2008). Gallardo et al (2011) determined that the presence of preferred sensory characteristics increases the likelihood of re-purchase; consumers were willing to pay an extra 19-25 cents/kg for higher quality pears.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the existing studies that have focused on consumers' sensory evaluation of pears are outdated and centered primarily around traditional pear cultivars (Elkins et al 2008;Gamble et al 2006;Kappel et al 1995;Konopacka et al 2015;Manning 2009;Turner et al 2005). In contrast, our study places its focus on a more recent selection of cultivars.…”
mentioning
confidence: 99%
“…Studies seeking to identify the cultivars with optimal quality sensory attributes have been conducted in different parts of the world. In the United States, Elkins et al (2008) conducted consumer sensory evaluations of European pear that were commercially available, along with pear selections from breeding programs. These cultivars included Williams, Sunrise, Abate Fetel, Cinnamon, Concorde, Rosemarie, Taylors Gold, and Blake's Pride.…”
mentioning
confidence: 99%
“…Flavor is sweet to subacid, being slightly less acidic than 'Bartlett' and 'Clapp's Favorite', and lightly aromatic, slightly less so than 'Bartlett' but more so than 'Clapp's Favorite'. Consumer ratings of flavor, appearance, and overall quality have been comparable to or higher than 'Bartlett', 'Conference', and other cultivars (Elkins et al, 2008).…”
Section: Descriptionmentioning
confidence: 75%